Impact of capital structure on firm value: evidence from listed hotels and travels industry in sri lanka - Vani, S.; Anushiya, A.; Nimalatheepan, S. (University of Jaffna, 2016)
Capital structure is one of the most complex areas of financial decision making because of its interrelationship with other financial decision variables. Capital structure choice is an important decision for a firm. It is important not only from returns maximization point of view, but also because this decision has a great impact on a firm's ability to successfully operating competitive environment. The capital structure and its impact on the value of the firm is one of the most discussed issues of corporate governance. The present study examines the Impact of capital structure on firm value among the listed hotels and travels companies in Sri Lanka. The various variables were used to measure the impact of capital structure on firm value. Such as, long term debt ratio (LDR, and Equity ratio (ER) as independent proxies whereas earning per share (EPS) and price earnings ratio (P/E Ratio) are considered as dependent proxies. The data obtained from the published annual financial reports and the authorized Colombo Stock Exchange data from 2010/2011 to 2014/2015, since the sample size in this study constitute the 20 companies by randomly selected among the 41 listed hotels and travels companies. Secondary data was collected from annual financial report of selected companies, in order to answer the research questions. Descriptive statistics, Person's correlation, and regression analysis are used for analysis with the SPSS 20 versions. The results revealed that, ER is significantly impact on Price earning ratio (p=0.001). Moreover ER has significantly positive correlated with P/E ratio at the significant level 1%.
Keywords: Capital structure; Debt; equity; Firm value; Hotels and travels companies